Doubly bi-allelic variants of MTHFR and MTHFD1 in a Chinese patient with hyperhomocysteinemia and failure of folic acid therapy - Liu, Yu-Xing; Ding, Man-Hua; Sheng, Yue; Sun, Meng-Fei; Liu, Lv; Zhang, Yang (Frontiers in Genetics, 2023)
Background: Hyperhomocysteinemia (HHcy) is a risk factor for thromboembolic disease. Defects in one-carbon metabolism (1-CM)-related genes, such as methylenetetrahydrofolate reductase (MTHFR), methylenetetrahydrofolate dehydrogenase, cyclohydrolase, and formyltetrahydrofolate synthetase 1 (MTHFD1), can cause HHcy and may also affect the efficacy of folic acid therapy. The details of mechanisms are yet to be further investigated. Method: We described a Chinese family with hereditary HHcy. The proband suffered from severe thromboembolic disease and experienced failure of folic acid therapy. Two sons of the proband were also diagnosed with HHcy but were sensitive to folic acid therapy. Whole-exome sequencing (WES) was conducted to evaluate the genetic lesion of this family. Results: Compound heterozygous variants (a common polymorphism, p. A222V, and a novel variant, p. C631*fs*1) of the MTHFR gene and a homozygous missense variant (p. K134R) of the MTHFD1 gene were identified in the proband. The two sons, with successful intervention, only harbored the homozygous p. A222V variant of the MTHFR gene. Conclusion: The clinical manifestations and genetic research synergistically confirmed the diagnosis of HHcy and clarified the failure of folic acid therapy in the proband caused by doubly bi-allelic variants of the MTHFR and MTHFD1 genes. Our study increased our understanding of the molecular basis of 1-CM-related gene defects on folic acid therapy in HHcy.